Prevalence of PTSD symptoms among police officers in Iceland : factors related to symptoms - Kristjana Kristinsdóttir 1987- (2018)
Post-traumatic stress disorder can develop after exposure to trauma. Repeated exposure to trauma increases the likelihood of developing PTSD. Police officers frequently find themselves in potentially traumatic situations. Studies have shown that police officers are at increased risk as a profession to develop PTSD symptoms and the prevalence is slightly higher than in the general population. This study focuses on the prevalence of PTSD symptoms among Icelandic police officers and what factors are related to the PTSD symptoms. A questionnaire was sent to all police officers in Iceland that measured demographics, symptoms of PTSD, as well as known risk and protective factors such as social support at work and social support from friends and family. Results showed that 19,8% of respondents showed clinical signs of PTSD. The following factors were found to be most strongly correlated to PTSD symptoms: depression, anxiety, burnout and social support at work. Interaction between the effects of social support and burnout on PTSD symptoms suggests that social support can mediate the effects between PTSD symptoms and burnout. Low social support at work seems to have a very negative impact on police officers. A longitudinal study is required to establish a causal relationship between the variables.